"Forced to Care" at the Neoliberal University: Invisible Labour as Academic Labour Performed by Black Women Academics in the South African University. Issue 3 (2nd October 2019) - Magoqwana, Babalwa; Maqabuka, Qawekazi; Tshoaedi, Malehoko
ABSTRACT: Higher education in South Africa faces the challenge and complexities of expanding to include a Black (Indian, Coloured and African) majority that was previously denied access. At the same time, global capitalism is entrenching neoliberal cultures, forcing institutions of higher education to restructure their academic labour processes into a quantifiable "assembly line", producing more outputs with fewer resources. In addition to typical research responsibilities that form part of standard academic labour, most administrative tasks have also been delegated to teaching faculty members. Exploring the biographical experiences of the authors, this paper argues that neoliberalism and corporatization of the university results in the performance of "invisible labour" (Wichroski, M.A. 1994. "The secretary: invisible labour in the work world of women". Human Organisation, 53(1): 33–41) by black women academics. This form of labour is unrewarded. Beyond the invisible expectations of being "role models" to students and peers, Black African women academics feel morally pressured to engage in "care work", a role that is stereotypically associated with their social and cultural backgrounds. Similar to domestic roles historically associated with working-class Black African women in South Africa, this form of invisible labour is not recognized and is thus unpaid. It is not captured by the university performance metric systems, and therefore has no significant value for academic promotion or prestigious university awards. This has consequences for the occupational structure of South African universities, contributing to the perpetual relegation of Black African women to the bottom of the institutional hierarchy. Similar to the apartheid era, Black African women are thus excluded from structures of power and influence, remaining the academic housekeepers —forced to care generously with few resources or reward.